2018
DOI: 10.3390/su10030626
|View full text |Cite
|
Sign up to set email alerts
|

The WHS Designation—A Factor of Sustainable Tourism Growth for Romanian Rural Areas?

Abstract: The presence of World Heritage Sites has been frequently used as a mean of tourism promotion and increased attractiveness. However, previous studies showed contradictory results regarding the territorial impact of World Heritage Sites, and very few researchers discussed their impact in Eastern Europe. This paper examines how the presence of World Heritage Sites in rural localities influenced the tourism growth and sustainable development in Romania after 2000. Independent Sample t-test was used to analyse the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Chang [30] suggested that tourism can only ease the pressure of rural decline, rather than make great impacts on the growth of local economy, his findings being in line with the vision of short-term impact of Loukissas [23]. Baum [46] considers that, outside of the traditional tourist destinations and far from big cities, tourism is not strong enough for supporting the diversification of rural economy, accessibility being the main supporting factor for tourism development [47,48], more important than even the local heritage [49].…”
Section: Tourism As a Factor For Sustainable Development Of Rural Areasmentioning
confidence: 78%
See 1 more Smart Citation
“…Chang [30] suggested that tourism can only ease the pressure of rural decline, rather than make great impacts on the growth of local economy, his findings being in line with the vision of short-term impact of Loukissas [23]. Baum [46] considers that, outside of the traditional tourist destinations and far from big cities, tourism is not strong enough for supporting the diversification of rural economy, accessibility being the main supporting factor for tourism development [47,48], more important than even the local heritage [49].…”
Section: Tourism As a Factor For Sustainable Development Of Rural Areasmentioning
confidence: 78%
“…We used Mann-Whitney U test, also called Wilcoxon rank-sum-a nonparametric test of the null hypothesis which does not require the assumption of normal distribution-to determine whether two independent samples have the same distribution or not. A similar method, however based on independent t-test has been successfully used in a recent study on the Romanian rural area for the identification of the impact of the presence of World Heritage Sites on sustainable development indicators [49].…”
Section: Data Processingmentioning
confidence: 99%
“…This situation is contradicting the ideas regarding the power of WHSs to promote the host country and to attract an increased number of tourists. The recent study of Iatu et al (2018) confirms Romania's position and its low ability to use WHSs in developing tourism. The only positive aspect is that Romanian rural WHSs are not plagued by excessive visitation and still have the time to envisage proper site management in order to avoid this problem.…”
Section: Resultsmentioning
confidence: 64%
“…While some exceptions exist, like the case of Viscri presented by Iorio and Corsale (2014), the majority of Romanian WHS localities do not properly exploit their tourist potential, a situation confirmed by Iatu et al (2018). In the cases of three communes (out of the 32 investigated), the local communities appear not to be willing to host tourists, having no registered lodging in 2005 and 2016, situation also pointed out by Pop and Coros (2016).…”
Section: Discussionmentioning
confidence: 81%
“…Inherent to the calls for sustainable development are concerns over implementation of the WH system's standards within developing countries, with elements of the discourse directed to promotion of conservation and sustainable development strategies that enable greater engagement with local communities (see for example, Chechi, ; Gullino et al, ; Halim & Ishak, ; Han et al, ; Larcher et al, ; La Rosa et al, ; Liu, ; Lixinski, ; Macheka, ; Owosuyim, ; Roders & van Oers, ). Consideration of local communities incurs identification of the stakeholders involved in management of a WH site, demarcating WH sites as venues bridging actors spanning global, national, and local levels (see for example, Allen & Lennon, ; Conradin & Hammer, ; Gullino et al, ; Iatu, Ibanescu, Stoleriu, & Munteanu, ; Nicholas & Thapa, ; Shende, ).…”
Section: Literature Review and Framing Sri Ksetra's Sustainable Develmentioning
confidence: 99%